Putative cis-Acting Stem-Loops in the 5′ Untranslated Region of the Severe Acute Respiratory Syndrome Coronavirus Can Substitute for Their Mouse Hepatitis Virus Counterparts - Kang, Hyojeung (American Society for Microbiology, 2006)
Consensus covariation-based secondary structural models for the 5′ 140 nucleotides of the 5′ untranslated regions (5′UTRs) from mouse hepatitis virus (MHV) and severe acute respiratory syndrome coronavirus (SCoV) were developed and predicted three major helical stem-loop structures, designated stem-loop 1 (SL1), SL2, and SL4. The SCoV 5′UTR was predicted to contain a fourth stem-loop, named SL3, in which the leader transcriptional regulatory sequence (TRS) is folded into a hairpin loop. cDNAs corresponding to MHV/SCoV chimeric genomes were constructed by replacing the complete MHV 5′UTR with the corresponding SCoV sequence and by separately replacing MHV 5′UTR putative SL1, putative SL2, TRS, and putative SL4 with the corresponding SCoV sequences. Chimeric genomes were transcribed in vitro, and viruses were recovered after electroporation into permissive cells. Genomes in which the MHV 5′UTR SL1, SL2, and SL4 were individually replaced by their SCoV counterparts were viable. Chimeras containing the complete SCoV 5′UTR or the predicted SCoV SL3 were not viable. A chimera containing the SCoV 5′UTR in which the SCoV TRS was replaced with the MHV TRS was also not viable. The chimera containing the entire SCoV 5′UTR failed to direct the synthesis of any virus-specific RNA. Replacing the SCoV TRS with the MHV TRS in the MHV/5′UTR SCoV chimera permitted the synthesis of minus-sense genome-sized RNA but did not support the production of positive- or minus-sense subgenomic RNA7. A similar phenotype was obtained with the MHV/SCoV SL3 chimera. These results suggest a role for the TRS in the replication of minus-sense genomic RNA in addition to its known function in subgenomic RNA synthesis.